A method for characterizing short-range molecular order in amorphous starch. (15th August 2020) - Liu, Xia; Luan, Huiyu; Jinglin, Yu; Wang, Shuo; Wang, Shujun; Copeland, Les
Graphical abstract: Highlights: A method has been developed to analyze order structure in amorphous starch. Raman spectroscopy was used to analyze the local order in amorphous starch. X-ray diffraction was used to characterize the local order in amorphous starch. The methods are useful to characterize structure-function relationship of starch. Abstract: This study presents a new method for characterizing short-range molecular order in amorphous starch using Raman spectroscopy and wide-angle X-ray diffraction (XRD). Amorphous wheat and potato starch samples with different degrees of short-range molecular order were prepared by heating starch:water mixtures ranging from 1:1 to 1:19 at 100 °C for 10 min. The XRD and 13 C CP/MAS NMR spectroscopy analyses showed that all starch samples had lost their long-range crystallinity and from that perspective were considered to be gelatinized. The peak area and intensity of the Raman bands at 480, 1131 and 1080 cm −1 and the full width at half maximum (FWHM) of XRD peaks at 16.7 and 20.7° (2θ) were correlated strongly to the degree of short-range molecular order in amorphous starch. On the basis of these relationships, we propose a method to analyze the short-range molecular order in amorphous starch, and thereby better characterize its properties.